Fatores associados a difusão da epidemia de Covid-19 - Confins (Confins)
The maps in this text seek to show what factors are associated with the Covid-19 epidemic, at least in the patterns of its spatial distribution. Their aim is to check whether there is a correlation between the distribution of the disease’s cases known as of June 14, 2020 and that of the factors considered, individually or jointly (through a PCA factor analysis and an ascending hierarchical classification, CAH) to look for causal relationships, which will then have to be analysed and proven by other methods